A Retrospective Comparison of 3-Factor Prothrombin Complex Concentrate Products for Warfarin Reversal. (July 2020) - Jones, G. Morgan; Cave, Brandon; Cook, Ryan
Background and Purpose: Current guidelines suggest that 3-factor prothrombin complex concentrate is a possible alternative to 4-factor products for the emergent reversal of bleeding secondary to warfarin. While multiple observational studies have evaluated various forms of 3-factor prothrombin complex concentrate individually, no study has compared the efficacy of the 2 products. The purpose of this study is to compare the efficacy and safety of Bebulin™ and Profilnine™ for the emergent reversal of warfarin-associated major bleeding. Methods: We conducted a retrospective cohort study of patients receiving both Bebulin™ and Profilnine™ at an urban, academic medical center with comprehensive stroke center designation and a neurosurgical center of excellence. All patients were treated at a single center that utilized a fixed, weight-based dosing protocol. The primary outcome was the percentage of patients in each group achieving a goal international normalization ratio of 1.4 or less. Results: There was a significant difference in goal international normalization ratio achieved favoring Bebulin™ (85.5% vs 27.3%; P < .001) over Profilnine™. Median dose per kilogram of actual body weight was the same between the groups. When we assessed results by baseline™ international normalization ratio subgroup, more patients in the Bebulin™ group achieved goal when baseline values were 6 or less. No thrombotic events were documented in either group. Conclusions: We found that patients treated with Bebulin™ experienced significantly higher rates of successful international normalization ratio reversal when compared to those who received Profilnine™. Further research is needed to determine the comparative efficacy between the 2 agents.